Movement behaviours and survival of largetooth sawfish, Pristis pristis, released from a public aquarium. Issue 12 (23rd August 2020) - Buckley, Kathryn A.; Crook, David A.; Einoder, Luke D.; Pillans, Richard D.; Smith, Liam D. G.; Kyne, Peter M.
Abstract: Public aquaria globally display numerous threatened fish species captured from wild populations. Potential impacts of harvests are rarely evaluated despite the need for improved management and conservation practices. Sawfishes (Family Pristiidae) are one of the world's most at‐risk fish families. Most commonly displayed (30+ wild caught individuals) is the Critically Endangered largetooth sawfish, Pristis pristis . Two Australian aquaria release captive P. pristis to the wild as they outgrow displays, intending to offset impacts of the original harvests. The fate of released sawfish is unknown. Using acoustic telemetry, the behaviour (rates of movement, patterns of habitat use) and survival of aquarium released sawfish ( n = 5) were compared to a control group of wild sawfish ( n = 5). Aquarium sawfish had reduced rates of movement, were more sedentary, and occupied smaller activity spaces than wild sawfish; but diel activity and habitat use patterns were similar. Collectively, mortality was high. Two aquarium sawfish survived to the end of the monitoring period (391 days and 117 days, respectively), and no wild sawfish survived. The mean duration of survival for aquarium and wild sawfish was 157 and 58 days, respectively. Whilst captivity affected behaviours, the lower mortality rates of aquarium sawfish indicates that releases may partially offset the impact of the original harvest. Further data are required to investigate potential long‐term ecological impacts. If P. pristis are to be used for aquarium displays, the best conservation outcomes could be achieved by harvesting in the first year of life when natural mortality is highest, followed by release into the freshwater reaches of the natal river where predation risk may be minimized. Size on release should be less than ~2, 800 mm total length to allow for migration from the river system as part of their natural life cycle.